2024
DOI: 10.1029/2023ms003840
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Global Ocean Biogeochemistry Models for Ocean Carbon Sink Estimates in RECCAP2 and Recommendations for Future Studies

Jens Terhaar,
Nadine Goris,
Jens D. Müller
et al.

Abstract: The ocean is a major carbon sink and takes up 25%–30% of the anthropogenically emitted CO2. A state‐of‐the‐art method to quantify this sink are global ocean biogeochemistry models (GOBMs), but their simulated CO2 uptake differs between models and is systematically lower than estimates based on statistical methods using surface ocean pCO2 and interior ocean measurements. Here, we provide an in‐depth evaluation of ocean carbon sink estimates from 1980 to 2018 from a GOBM ensemble. As sources of inter‐model diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 210 publications
0
10
0
Order By: Relevance
“…The inferred northward C ant transport at the southern boundary between Atlantic and Southern Oceans obtained for each of the nine GOBMs with Simulations A and D shows a high correlation (r 2 = 0.61; p-level < 0.01) with the maximum AMOC values at 26°N of each of these GOBMs (Figure S12 in Supporting Information S1), indicating that the northward physical transport is the main driver of the northward C ant transport. We note additionally that, in comparison with observations, the GOBMs tend to underestimate the maximum AMOC values at 26°N (Figure S12 in Supporting Information S1) and hence the inferred northward C ant transport (Terhaar et al, 2024).…”
Section: Anthropogenic Co 2 Uptake and Lateral Transportmentioning
confidence: 48%
See 4 more Smart Citations
“…The inferred northward C ant transport at the southern boundary between Atlantic and Southern Oceans obtained for each of the nine GOBMs with Simulations A and D shows a high correlation (r 2 = 0.61; p-level < 0.01) with the maximum AMOC values at 26°N of each of these GOBMs (Figure S12 in Supporting Information S1), indicating that the northward physical transport is the main driver of the northward C ant transport. We note additionally that, in comparison with observations, the GOBMs tend to underestimate the maximum AMOC values at 26°N (Figure S12 in Supporting Information S1) and hence the inferred northward C ant transport (Terhaar et al, 2024).…”
Section: Anthropogenic Co 2 Uptake and Lateral Transportmentioning
confidence: 48%
“…Further, using Earth System Models, Goris et al (2023) showed that the AMOC-strength drives the simulated seasonal variability in the North Atlantic. Altogether, this suggests that the Global Biogeochemical Cycles 10.1029/2023GB007862 underestimation of the AMOC in the GOBMs (Terhaar et al, 2024) could be an underlying cause for the underestimation of the role of biogeochemical variability for both IAV and seasonality by the GOBMs in the NA SPSS.…”
Section: Temporal Variability In Sea-air Co 2 Fluxes In Models and Pc...mentioning
confidence: 92%
See 3 more Smart Citations